2011
DOI: 10.5546/aap.2011.e126
|View full text |Cite
|
Sign up to set email alerts
|

Hibernoma: tumor retroperitoneal de grasa parda. Informe de un caso pediátrico

Abstract: Presentación de casos clínicos RESUMENEl hibernoma es un raro tumor benigno de los tejidos blandos, compuesto por grasa parda, tejido que predomina en animales que hibernan y de allí su nombre. Debido a su infrecuencia en Pediatría y a su diagnóstico complejo, presentamos un paciente de 3 meses de edad, con diagnóstico de tumor abdominal. Los exámenes por ecografía y tomografía computada demostraron un tumor retroperitoneal de carácter infiltrativo, vascularizado y con características lipomatosas. La exéresis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
2
0
3
Order By: Relevance
“…Very few cases of hibernoma in Paediatric age group have been reported. A retoperitoneal Hibernoma was reported in a three old patient by Collado et al in 2011 [9]. Khattala K et al [10] reported a case of cervical hibernoma arising from supraclavicular fossa in a two year old boy.…”
Section: Discussionmentioning
confidence: 94%
“…Very few cases of hibernoma in Paediatric age group have been reported. A retoperitoneal Hibernoma was reported in a three old patient by Collado et al in 2011 [9]. Khattala K et al [10] reported a case of cervical hibernoma arising from supraclavicular fossa in a two year old boy.…”
Section: Discussionmentioning
confidence: 94%
“…Macroscopically, they are characterised by well-defined, slightly lobulated, shiny masses, ranging in colour from yellow to brown [6]. To our knowledge, a total of 15 cases of retroperitoneal hibernoma have been published in the literature (Table 1), 25 in total if we add the 10 reported in the series by Furlong et al [4,5,9,[12][13][14][15][16][17][18][19][20][21][22][23][24]. Of the 15 published in isolation, 11 were in women and 4 in men.…”
Section: Discussionmentioning
confidence: 99%
“…El lipoblastoma se va a presentar en la gran mayoría de los casos en la infancia temprana y generalmente no se asocia a otros síndromes 1 . A diferencia del resto de los tumores de tejido a adiposo, como el hibernoma que se presenta con mayor frecuencia entre los 30-40 años y el liposarcoma en mayores de 40 años, siendo extremadamente raro en menores de 10 años 6,9,10 .…”
Section: Discussionunclassified